Performance analysis of point-to-multipoint WiMAX network / Khadijah Ismail - Ismail, Khadijah (2007)
The maturing of fixed Worldwide Interoperability for Microwave Access, WiMAX technology is making possible a number of exciting new applications that previously were limited by cost, distance and throughput requirements. With the latest wireless innovations, fixed wireless applications can now go beyond mere short-range data communications, and could be possibly implemented in a secure manner. Superior outdoor performance, proven Quality of Service, QoS and solid security enable WiMAX to support valuable multimedia applications, such as network video for surveillance. The IEEE 802.16 WirelessMAN standard which has emerged as Broadband Wireless Access, BWA solution, is promising to meet all such requirements and becoming the most popular way for wireless communication. The IEEE 802.16 advantages includes variable and high data rate, last mile wireless access, point to multipoint communication, large frequency range and QoS for various types of applications. This thesis presents a performance analysis of Medium Access Control, MAC layer of IEEE802.16 using OPNET DOCSIS Module. IEEE 802.16 was largely based on Data Over Cable Service Interface Specification 1.1, DOCSIS 1.1, hence the basic protocol operation and QoS features of both protocols are the same. The impacts of the different WiMAX scheduling features on the different traffic classes are thoroughly investigated and analyzed. 1EEE802.16 MAC protocol includes QoS guarantees, but it does not provide a complete solution and does not describe how to schedule traffic to fulfill the QoS requirements specifically. Therefore, scheduling policies at the Subscriber Station, SS and the Base Station, BS are proposed in this project. Detailed analysis of the network performance is provided through extensive simulations.